Effectiveness of Synthetic Biology to Diminish Global Biological Diversity Loss: A Comprehensive Review - Dutta, Shourav (International Journal of Scientific Research in Biological Sciences, 2023)
The status of biological diversity and genetic variations across the globe is changing faster due to various climatic and anthropogenic disturbances. Numerous research projects have revealed that traditional conservation approaches and protected area networks are inadequate to reduce the biodiversity loss rate. Synthetic biology is the most effective option to preserve biological diversity and increase sustainable protection of species in the existing environment through genetically improved materials. Synthetic biology is a field that connects research with practice, transforms ideas into innovations, offers the potential to resolve conservation problems via genome editing, and thinks strategically and tactically at the same time. This paper is prepared based on an extensive literature survey and explores synthetic biology`s effectiveness for the overall conservation practices of global biodiversity. The study revealed a communication gap and inadequate involvement between the conservation and synthetic biology communities. This paper broadly elucidates the potential applications of synthetic biology and discloses the necessity of optimistic synthetic biology technologies for protecting the global biological diversity.